Private Enforcement and Opt-out System Risks, Rewards and Legal Safeguards - Ramos, Maria Elisabete (2018)
The EU Antitrust Damages Actions Directive does not include provisions for collective redress. Each EU member state is free to provide national regulation on this matter. The Portuguese legal system provided regulation on actio popularis since 1995. The ‘rational apathy’ of individual consumers may lead to non-reparation of damage and be of significant benefit for the company that is in breach of the law. The opt-out models solve the crucial economic problem caused by a large number of consumers or clients who have suffered a small loss because of competition law infringements. Under those circumstances, it is rational to be apathetic, because it can be foreseen that the cost of filing for compensatory damages will exceed the recovery obtained from the defendant. Such rational apathy of the parties injured by competition law infringements favours the wrongfully acting companies by not extracting their illegal gains from them. By not requiring the active consent of each of the claimants, the opt-out model is able to override rational apathy of consumers.